Aktivitas Berjalan Di Atas Papan Titian Terhadap Perkembangan Motorik Kasar Anak Usia 5-6 Tahun - Ayu Halimatus Sakdiyah; Dita Yuliastrid; Noortje Anita K; Indra Himawan Susanto (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2024)
Gross motor skills are the ability to move the body using large muscles, most or all of the body's gross motor skills are needed by children to sit, kick, run, go up and down stairs. The aim of this research is to determine the effect of walking on a boardwalk on gross motor development in children aged 5-6 years. The method used in this research is quasi-experiment. The design of this research is pretest and posttest (the one group pretest posttest design). This research was conducted at the Asfiyah Lidah Wetan Islamic Kindergarten, Lakarsantri District, Surabaya, East Java. The practice time in the field is 7 weeks with a training duration of 2 times per week. The population in this study were all students at Asfiyah Islamic Kindergarten who were active in walking on the boardwalk with a total of 45 students. The sampling technique in this research is total sampling, namely a sampling technique with the number of samples equal to the population. The research instruments that I carried out were using tests of walking forward with arms outstretched, walking sideways with arms outstretched, walking forward with hands on the waist, walking forward with hands folded in front of the chest, and standing on one leg in an airplane stance. The collection technique in this study used Wilcoxon. The conclusion in this study shows that there is a significant Sig (2-tailed) influence of the activity of walking on the boardwalk on the gross motor development of children aged 5-6 years at the Asfiyah Lidah Wetan Islamic Kindergarten using the outstretched hands forward walking test, walking sidewaysarms outstretched, walking forward with hands on your waist, walking forward with your hands folded in front of your chest, and standing on one leg in an airplane stance. It is proven that the Sig value. (2-tailed) of the five indicators < 0.05.